2021
DOI: 10.1038/s41438-021-00480-8
|View full text |Cite
|
Sign up to set email alerts
|

sRNAanno—a database repository of uniformly annotated small RNAs in plants

Abstract: Small RNAs (sRNAs) are essential regulatory molecules, and there are three major sRNA classes in plants: microRNAs (miRNAs), phased small interfering RNAs (phased siRNAs or phasiRNAs), and heterochromatic siRNAs (hc-siRNAs). Excluding miRNAs, the other two classes are not well annotated or available in public databases for most sequenced plant genomes. We performed a comprehensive sRNA annotation of 143 plant species that have fully sequenced genomes and next-generation sequencing sRNA data publicly available.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 23 publications
(32 reference statements)
0
58
0
Order By: Relevance
“…SNP density and nucleotide diversity were calculated only for SNPs extracted from the 'Feizixiao' VCF file. Similarly, sRNA and LTR densities were calculated from small RNA annotation 73 and LTR annotation files, respectively. All the above 'Feizixiao' genome features were viewed in Circos plotted using TBtools 68 .…”
Section: Genome Assembly Reference Genome Assemblymentioning
confidence: 99%
“…SNP density and nucleotide diversity were calculated only for SNPs extracted from the 'Feizixiao' VCF file. Similarly, sRNA and LTR densities were calculated from small RNA annotation 73 and LTR annotation files, respectively. All the above 'Feizixiao' genome features were viewed in Circos plotted using TBtools 68 .…”
Section: Genome Assembly Reference Genome Assemblymentioning
confidence: 99%
“…A total of 134 miRNA-encoding genes were identified in the present dataset ( Figure 2 ) [ 21 ], representing 30 recognized MIRNA gene families. Database comparisons revealed that 109 of the 134 genes had been previously identified in oil palm ( accessed on 5 January 2022), whereas the remaining 25 genes were previously unreported in this species.…”
Section: Resultsmentioning
confidence: 99%
“…Its biogenesis also requires RNA Pol IV-mediated transcription and RDR2-mediated formation of dsRNA ( Parent et al, 2015 ). Finally, DCL3 processes the dsRNA into 24 nt siRNA duplexes, and HEN1 methylates the siRNA duplexes to form 24 nt hcsiRNA ( Chen et al, 2021a ; Figure 1C ). Biosynthesis of vsiRNA also requires the participation of DCLs, AGOs, and RDR proteins.…”
Section: Srna Biogenesismentioning
confidence: 99%
“…However, how to distinguish the origin of sRNA in this integral system has become a problem because both plants and fungal pathogens can produce sRNA. The genomes of most species have been sequenced, so the source of sRNA can usually be determined by homology search ( Chen et al, 2021a ). Using a sequential protoplast preparation method to purify fungal protoplasts from infected plant tissues, sRNAs that are transported from plant to fungal pathogen were identified ( Cai et al, 2018 ).…”
Section: Srna Functionsmentioning
confidence: 99%